Analisis Faktor Akuntansi dan Non Akuntansi dalam Memprediksi Peringkat Obligasi Perusahaan Manufaktur - SEJATI, GRACE PUTRI (BISNIS & BIROKRASI: Jurnal Ilmu Administrasi dan Organisasi, 2011)
The research aims to explain the influence of accounting and non-accounting factors in predicting the bonds level. This research uses quantitative approach and takes samples by using purposive sampling technique, that is bonds of manufacture companies listed in Jakarta Stock Exchange (Now is known as Indonesian Stock Exchange, after mergered with Surabaya Stock Exchange) and listed in the level of bonds issued by Pefindo in the period of 2003 to 2008. The result of the research shows that the accounting factor that affects the prediction of bonds level is growth, while the non-accounting level that does not affect the prediction of bonds level is auditor reputation.